Effectiveness of Ovitrap Tool Model Yellow Light with White Water Modification Sindang Kelingi District in 2021 - Rustam Aji; Agussalim; Gustomo Yamistada; Jessy Novita Sari (POLTEKKES KEMENKES PADANG, 2023)
Indonesia is a tropical area which is an excellent place for mosquito breeding, because the temperature, weather, and seasons in Indonesia are very supportive in the mosquito breeding process, so that the mosquito population becomes high and very dangerous for human life, the existence of vectors that are detrimental to human life, because Mosquitoes are vectors that cause and transmit diseases in human life. To control the mosquito population, it is necessary to eradicate it by reducing the mosquito population. This study aims to determine the effectiveness of the yellow light ovitrap model with a modified water bottle, in the intervention group and the control group. Observational research, cross sectional study design. Survey of mosquito locations on the terrace of the house. The survey data were analyzed using the chi-square test. The results of Chi-square analysis obtained P value = 0.08 > 0.05. So Ho is accepted and Ha is rejected, which means that there is no statistically significant relationship between the yellow light ovitrap and the modified water bottle. does not rule out the possibility of 2.33 times being found trapped mosquitoes.